Mortality outbreak by perch rhabdovirus in European perch (Perca fluviatilis) farmed in Italy: Clinical presentation and phylogenetic analysis. Issue 5 (8th March 2019) - Caruso, Claudio; Gustinelli, Andrea; Pastorino, Paolo; Acutis, Pier Luigi; Prato, Riccardo; Masoero, Loretta; Peletto, Simone; Fioravanti, Maria Letizia; Prearo, Marino
Abstract: This work reports a mortality outbreak, occurred in 2015 and affecting juveniles of European perch ( Perca fluviatilis L.) farmed in Italy. Perch rhabdovirus (PRV) was detected by viral isolation and biomolecular investigations. Phylogenetic analysis clustered our isolate into genogroup B, which also includes PRV isolates from Perca fluviatilis identified in France (2004–2009); diagnostic investigations also revealed opportunistic bacteria ( Aeromonas hydrophila ) and parasites ( Chilodonella piscicola ). Since, occasionally, PRV has been reported in the natural environment, which is often a source of eggs and broodstock for farms, it could be possible that both similar France and Italian isolate were imported from a same place elsewhere and have a common origin. Improving biosecurity measures (batch control) and disinfection of egg strings with an iodine‐based solution helps prevent apparent vertical transmission of PRV.